EFL Students’ English Language Development: In Participation of International Exchange Program - Ariyanti Ariyanti (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
This research is aimed to investigate students development in terms of their English speaking proficiency, vocabulary and pronunciation aspects in context of English as Foreign Language. Furthermore, six EFL students who become subject of this research are Indonesian students who are originally stil studying at University of Widya Gama Mahakam Samarinda, Indonesia. In this case, those students had an experience of participating an international program what so called by Sea-Teacher, one of priority programs under Southeast Asian Ministers of Education (SEAMEO) which its homebase is in Bangkok, Thailand. Moreover, in dept interview was applied to those six students in order to find out what sort of effects they acquire after participating the Sea-Teacher program. As a result, all of exchange students experience development in terms of their oral proficiency, vocabulary as well as pronunciation. Natural condition in using English as language of communication was formed when conversing with local people and teaching in classrooms. Research implication and suggestion are also noticed in this study.